Levels of interleukin-8 and catalase have correlations with zinc in healthy adults: Implications for inflammatory conditions - Arinola, Ganiyu Olatunbosun; Edem, Fabian Victory (Annals of Medical Research, 2021)
Aim: To determine the relationship between Zinc levels with different aspects of innate immunity [percentage leucocyte migration (%LM), intracellular killing (%NBT), plasma inflammatory cytokines (IL-6) and IL-8), plasma antioxidant enzymes (catalase, superoxide dismutase, myeloperoxidase, hydrogen peroxide) and nitric oxide] among healthy Nigerians.Material and Methods: In 50 healthy adults, two phagocytic indices [percentage leucocyte migration (%LM) and intracellular killing (%NBT)] were determined by microscopy; two inflammatory cytokines [Plasma interleukin 6 (IL-6) and 8 (IL-8)] were assessed using ELISA; respiratory burst indices [plasma catalase (CAT), superoxide dismutase (SOD), myeloperoxidase (MPO), hydrogen peroxide (H2O2) and nitric oxide (NO)] were evaluated by spectrophotometry. Zinc (Zn) was determined using Atomic Absorption Spectrometry. Phagocytic indices, cytokines and respiratory burst indices were correlated with plasma Zn levels using Spearmans Correlation analysis at P
Keywords: Cytokines; inflammation; intracellular infections; micronutrient Zn; phagocytosis